KLASIFIKASI DILALAH: ANALISIS DESKRIPTIF ATAS METODE PENUNJUKAN MAKNA DALAM ISTINBAT HUKUM ISLAM - Siti Rohani (Formad English Foundation NTB-Jakarta, 2024)
This study examines the concept of dilalah in the perspective of Islamic law with a focus on the classification of dilalah as a method of indicating meaning in legal istinbat. Usul fiqh scholars define this discipline through two main approaches. First, the approach based on the structure of the wording (takribi idlafi), namely